Subcutaneous pedicle propeller flap: An old technique revisited and modified! - Durga Karki; Nikhil Mehta; Ravi Prakash Narayan (Indian Journal of Plastic Surgery)
Background: Post-burn axillary and elbow scar contracture is a challenging problem to the reconstructive surgeon owing to the wide range of abduction and extension that should be achieved, respectively, while treating either of the joint. The aim of this paper is to highlight the use of subcutaneous pedicle propeller flap for the management of post-burn axillary and elbow contractures. Methodology: This is a prospective case study of axillary and elbow contractures managed at a tertiary care hospital using propeller flap based on subcutaneous pedicle from 2009 to 2014. Surgical treatment comprised of subcutaneous-based pedicle propeller flap from the normal tissue within the contracture based on central axis pedicle. The flap was rotated axially to break the contracture. The technique further encompassed a modification, a Zig-Zag incision of the flap, which was seen to prevent hypertrophy along the incision line. There was a mean period of 12 months of follow-up. Results: Thirty-eight patients consisting of 22 males and 16 females were included in this study among which 23 patients had Type II axillary contractures and 15 had moderate flexion contractures at elbow joint. The post-operative abduction achieved at shoulder joint had a mean of 168° whereas extension achieved at elbow had a mean of 175°. The functional and aesthetic results were satisfactory. Conclusion: The choice of surgical procedure for reconstruction of post-burn upper extremity contractures should be made according to the pattern of scar contracture and the state of surrounding skin. The choice of subcutaneous pedicle propeller flap should be emphasised because of the superior functional results of flap as well as ease to learn it. Moreover, the modification of propeller flap described achieves better results in terms of scar healing. There is an inter-positioning of healthy skin in between the graft, so it prevents scar band formation all around the flap.